2006
DOI: 10.1111/j.1747-0285.2006.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Aza‐scanning of the Potent Melanocortin Receptor Agonist Ac‐His‐d‐Phe‐Arg‐Trp‐NH2

Abstract: The melanocortin pathway is an important participant in the regulation of skin pigmentation, steroidogenesis, obesity, energy homeostasis, and exocrine gland function. Melanocortin agonists contain the putative sequence 'His-Phe-Arg-Trp', which has been designated as the 'message' sequence for melanocortin peptides, and this sequence has been hypothesized to adopt a bioactive reverse turn conformation. Exploring the relationship between its structure and biological activity, we report the synthesis and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
0
24
1
Order By: Relevance
“…To avoid multistep solution‐phase synthesis of N ‐Boc‐aza 1 ‐dipeptide building blocks, the activation of N ‐protected N ′‐alkyl carbazates was later employed in aza‐amino acid scanning (82,89–92). For example, N ‐(Fmoc)aza‐amino acid chlorides have been prepared from N ‐(Fmoc)hydrazine by reductive aminations with various aldehydes (89,91), followed by activation with phosgene, and incorporated into a variety of bio‐active peptide sequences: hCGRP antagonists (42), the tetrapeptide MCR agonist Ac‐His‐ d ‐Phe‐Arg‐Trp‐NH 2 (93), RGD peptides (94,95), GH‐releasing peptide‐6 (GHRP‐6) (96), and a peptide‐based persistently activated protein kinase B (PKB/Akt) inhibitor (91) (Scheme 6). In the latter study, microwave irradiation was found to significantly reduce reaction times during couplings of the N ‐Fmoc‐aza‐amino acid chlorides (91).…”
Section: Aza‐amino Acid Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid multistep solution‐phase synthesis of N ‐Boc‐aza 1 ‐dipeptide building blocks, the activation of N ‐protected N ′‐alkyl carbazates was later employed in aza‐amino acid scanning (82,89–92). For example, N ‐(Fmoc)aza‐amino acid chlorides have been prepared from N ‐(Fmoc)hydrazine by reductive aminations with various aldehydes (89,91), followed by activation with phosgene, and incorporated into a variety of bio‐active peptide sequences: hCGRP antagonists (42), the tetrapeptide MCR agonist Ac‐His‐ d ‐Phe‐Arg‐Trp‐NH 2 (93), RGD peptides (94,95), GH‐releasing peptide‐6 (GHRP‐6) (96), and a peptide‐based persistently activated protein kinase B (PKB/Akt) inhibitor (91) (Scheme 6). In the latter study, microwave irradiation was found to significantly reduce reaction times during couplings of the N ‐Fmoc‐aza‐amino acid chlorides (91).…”
Section: Aza‐amino Acid Scanningmentioning
confidence: 99%
“…In pursuit of selective agonists and antagonists of the five MCR subtypes to better characterize this family of G‐protein coupled receptors implicated in feeding behavior, metabolism, energy homeostasis, and skin pigmentation (97), as well as to develop treatments for obesity and skin cancer (98), the aza‐scan of the agonist Ac‐His‐ d ‐Phe‐Arg‐Trp‐NH 2 was performed delivering analogs exhibiting decreased potency on substitution of the central d ‐Phe 2 ‐Arg 3 residues with aza‐Phe 2 , aza‐Lys 3 , aza‐Orn 3 , aza‐Arg 3 , respectively, and similar potency relative to the parent peptide on replacement of the C ‐terminal Trp 4 with aza‐Nal‐1, aza‐Nal‐2, and aza‐Bip (93). In attempts to develop selective azapeptide inhibitors of the αIIb β 3 and αv β 3 integrins implicated in human tumor metastasis and tumor‐induced angiogenesis (94), aza‐amino acid scans were performed on the cyclic RGD‐pentapeptide, Cilengitide, cyclo [RGDf‐ N ‐(Me)V], and its parent peptide, cyclo [RGDfV], identifying cyclo [R‐aza‐GDfV], which retained selective nanomolar activity for the αvβ3 receptor (95).…”
Section: Aza‐amino Acid Scanningmentioning
confidence: 99%
“…Azapeptide analogs can thus show varying degrees of activity relative to their diastereomeric peptide counterparts. For example, in functional assays on HEK-293 cells stably expressing different mouse melanocortin receptor (MCR) subtypes (mMC1R, mMC3R, mMC4R, and mMC5R) replacement of aza-arginine for arginine in the melanocyte-stimulating hormone (MSH) tetra-peptide 5 gave [aza-Arg 3 ]MSH 6, which exhibited a drop of activity at the mMC1R that was less significant than that of the [D-Arg 3 ]MSH isomer; however, more significant losses of activity than both isomers on the other receptor subtypes ( Figure 2) [6]. In the interest of further exploring the adaptive chirality of nitrogen in an aza-peptide analog, we selected to make an aza-analog of the sugar substitute aspartame, because earlier studies had demonstrated that the S,S-and R,S-diastereomers (Figure 4) exhibited sweet and bitter tastes, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the solid‐phase synthesis of C‐terminal azapeptides has remained a challenge. Notably, a limited number of C‐terminal azapeptides have been previously synthesized using N ‐(Fmoc)‐aza‐amino acid and (Ddz)‐aza‐amino acid chlorides that were respectively prepared from N ′‐alkyl 9‐fluorenylmethyl and 2‐(3,5‐dimethoxyphenyl)propan‐2‐yl carbazates on activation with phosgene prior to coupling to the amine of the Rink amide resin . Side chain diversity is, however, limited in scope using this approach, which necessitates synthesis of hydrazine building blocks in solution ; moreover, the toxicity of phosgene and side products such as oxadiazole analogs from phosgene activation inhibits the versatility of this method .…”
Section: Scope and Commentsmentioning
confidence: 99%